Metacognitive Strategies Employed by Australian Award Scholarship (AAS) Awardees from Aceh in Preparing for the IELTS Test - Refa Malasari; Januarius Mujiiyanto; Rahayu Puji Hayanti (English Education Journal, 2024)
This study explores the role of metacognitive strategies in improving the IELTS scores of Australian Award Scholarship (AAS) awardees from Aceh, addressing a gap in research on effective preparation methods for high-stakes English language tests. The research aims to identify how metacognitive strategies enhance the IELTS preparation process and to determine which specific strategies are most beneficial for achieving higher scores. A mixed-methods approach was employed, combining quantitative data from questionnaires and qualitative insights from interviews and observations with AAS awardees. Participants' engagement in planning, monitoring, and evaluating their learning processes was analyzed.The findings indicate that the use of metacognitive strategies significantly improved the IELTS scores of the participants. Key strategies included detailed planning of study schedules, setting clear goals, continuous progress monitoring, and reflective practices to adjust learning methods. The study concludes that metacognitive strategies are highly effective in enhancing IELTS preparation, leading to better academic outcomes. This research highlights the critical role of metacognitive strategies in language learning and test preparation, providing a structured approach that helps learners stay motivated and adapt their methods for better results. The findings offer valuable insights for students, educators, and policymakers, emphasizing the need to integrate metacognitive strategy training into English language programs. This approach can enhance the effectiveness of IELTS preparation courses, leading to improved educational outcomes and contributing to the development of language education in society.